Implementasi Teori Difusi Inovasi Pada Digital Payment Application - Muhammad Ihsan Alifi; Maulia Pratiwi; Lista Faujiah; Rangga Galura Gumelar (Peneliti.net, 2023)
The research presented provides an explanation of how the theory of innovation diffusion applies to the process of using digital payment applications. This research was carried out by reading previous works that have been written on the subject that is now being investigated. The findings indicated that digital payment was an innovation that is widely adopted by the Early Adopters group. This group possesses a high level of opinion leadership, as can be seen from the provision of the role of testimonials to reduce doubts and uncertainty of innovation, in addition to knowledge and dissemination of innovations carried out. The results showed that digital payment was an innovation that was widely adopted by the early Adopters group.